Sprint speed measurement in a national rugby union academy: An equivalence study of three measurement systems, age, and playing position - Wright, A. R.; Weston, M.; Menzies, F. A.; Ramirez-Lopez, C.; Boyd, A. J.; Barrett, S.; Turner, A. P. (European Journal of Sport Science, 2026)
This study profiled the sprint speed of young male rugby union players in a national pathway academy, comparing different technologies for determining maximal velocity (Vmax), while also examining age-group and positional effects. Data were collected from 140 players using a 40 m sprint during a single testing day. The data included anthropometric measures (age, body mass, and height), split times (10 m, 20 m, 30 m, and 40 m), maximum momentum, Vmax, and time to Vmax (tVmax), captured across three measurement systems: timing gates, local positioning systems (LPS), and foot-mounted inertial measurement units (IMU). Effects were interpreted using equivalence testing. Here, regions of practical equivalence were informed by practitioner opinion of the acceptable amount of measurement error when measuring maximal speed and target change values for sprint times. Measurement comparisons showed practical equivalence only for Vmax between timing gates and LPS, suggesting they could be used interchangeably. All age-group and positional differences were not practically important with 10-m metre sprint times being practically equivalent between backs and forwards. Our findings emphasise the importance of measurement choice during speed profiling to inform speed and momentum development for young rugby players.